Kaedah Komunikasi Keluarga dalam Surah Āli ‘Imrān Ayat 159: Kajian Amalan Mualaf Cina di Selangor: Method of Family Communication in Surah Āli ‘Imrān Section 159: A Study of Chinese Mualaf Practice in Selangor - Abdul Rahman, Azirawati; Hj Siren, Nor Raudah; Md Yusoff, Yusmini (Jurnal Usuluddin, 2021)
Communication is one of important aspects in forming a happy and prosperous family. Poor communication in family would give negative effects on emotions and psychology of the family members. In this context, Islam has a complete solution to address all problems related to families’ matters which occur in daily life. This article discusses about family’s communication from Islamic perspective according to Surah Āli ‘Imrān verse 159. The study found that the style of communication suggested for Muslims family is around gentle and soft speaking, musyawarah and family’s relationship sustenance. The former communication approach is explained through six kinds of language methods mentioned in the Quran namely qaulan layyina, qaulan ma’rufa, qaulan sadida, qawlan karīmā, qaulan maysura and qaulan baligha. These methods of language were employed by the selected ten Chinese research informants through semi-structured interviews. Descriptive qualitative analysis was conducted thematically. The findings showed that all informants emphasized the importance of using these methods as means of getting attention, generating love and sustaining family relationships.